Efektivitas Case Base Learning dan Peran Curiosity Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis - Fitriani, Riska; Anggoro, Bambang Sri; Nabila, Siti Ulfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematical problem-solving ability is one of the essential competencies students need to master; however, in reality, many students still face difficulties in developing this skill. One effort to improve it is through the implementation of Case Base Learning while also considering affective factors such as curiosity. This study aims to examine the effect of Case Base Learning and curiosity on students’ mathematical problem-solving ability. The research employed a quantitative approach with a quasi-experimental design. The population consisted of all ninth-grade students of SMP Negeri 1 Abung Semuli, with a total sample of 65 students selected using cluster random sampling. The sample consisted of two classes: class IX H as the experimental class, which applied Case Base Learning, and class IX F as the control class, which applied Direct Instruction. The instruments used were a mathematical problem-solving test and a curiosity questionnaire. Data analysis was conducted using two-way ANOVA with prerequisite tests, namely normality and homogeneity tests. The results of the study revealed that: (1) Case Base Learning was more effective than Direct Instruction in improving students’ mathematical problem-solving ability, (2) curiosity had a significant role in enhancing students’ mathematical problem-solving ability, and (3) there was no interaction between Case Base Learning and curiosity in influencing students’ mathematical problem-solving ability.